The Role of the Women and Children Service Unit in Handling Cases of Sexual Violence Against Children - Sanjaya, Aurel Frisky; Surahman, Surahman (Bacarita Law Journal, 2025)
Sexual violence against children is a form of criminal act that has a serious impact on the victim, both physically and psychologically. Although Indonesia is a country of law that upholds justice, the reality is that there are still various obstacles in law enforcement against perpetrators of sexual violence against children. The Samarinda City Resort Police Women and Children Service Unit plays an important role in handling these cases, including in providing assistance to victims and processing cases to the legal settlement stage. However, in its implementation, the Women and Children Service Unit still faces various obstacles, both in terms of technical, human resources, and social factors. This study aims to analyze the role of the Women and Children Service Unit of the Samarinda City Resort Police in handling sexual violence against children and identify inhibiting factors in the implementation of their duties. This study uses an empirical juridical method with a qualitative approach, where data is obtained through interviews, observations, and document studies. The results of the study show that although the Women and Children Service Unit has carried out various efforts in handling cases of sexual violence against children, there are a number of obstacles that hinder the effectiveness of handling cases. These obstacles include the lack of expert personnel, limited facilities, delays in the issuance of visum results, as well as social factors such as stigma and fear of the victim's family to report. In addition, the limited coordination between relevant institutions is also a challenge in the fast and effective law enforcement process. Based on the findings of this study, efforts are needed to improve in various aspects, including the addition of professionals, the provision of more adequate facilities, and education to the public to be more aware of the importance of reporting cases of sexual violence against children, so it is hoped that the Women and Children Protection Unit can be more optimal in carrying out its duties to protect children's rights and ensure justice for victims of sexual violence.